Integrating Listening: Speaking Tasks in EFL Classrooms - Kalayo Hasibuan; Annisa Falasifa; Jannatul Hillati (ANTHOR: Education and Learning Journal, 2026)
The integration of listening and speaking skills in English as a Foreign Language (EFL) classrooms has become an effective pedagogical approach to enhancing learners’ communicative competence. This paper explores the role of integrated listening and speaking activities in improving students’ language performance, participation, and confidence in using English. Listening activities provide meaningful language input, while speaking tasks offer opportunities for learners to actively produce language and express their ideas in communicative contexts. The integration of these skills facilitates the development of essential language components, including vocabulary, pronunciation, fluency, and listening comprehension, in a more holistic and interconnected manner. In classroom practice, various interactive strategies, such as group discussions, role-plays, interviews, and task-based activities, can be employed to create engaging and student-centered learning environments. A review of the literature indicates that integrated listening and speaking instruction positively influences learners’ motivation and communicative ability. Nevertheless, successful implementation requires careful task design and effective classroom management to address challenges such as limited instructional time and varying levels of student proficiency. Therefore, integrating listening and speaking skills is recommended as an effective strategy for promoting meaningful language learning and improving students’ communicative competence in EFL settings.